Chhaupadi and mobility & leadership of women: a study on effects of Chhaupadi on mobility and leadership of women in Karnali, Nepal. - Dahal,Bhola Prasad
SUMMARY: 'Chhaupadi' is a deeply rooted socio-cultural practice followed in mid & far western region. In such practice, the menstruating women and girls are considered as 'impure' and they have to follow several restrictions and barriers. In many communities, the menstruating women and girls have to stay in isolated place like Chhau-hut, Cow-hut or separate room in the house. They are restricted to enter into home, consume nutritious foods, touch male family members, use similar toilets and water taps, participate in social functions, and other essential daily activities. All these barriers and restriction are directly affecting the life and wellbeing status of women and girls; and ultimately impact on overall livelihood. While considering the 'Chhaupadi' as harmful practice, the GON promulgated a directive regarding its' elimination in 2007. Similarly, several development organization, local institutions, CBOs, and right actors are raising the voice against this mal practice; and working to address the issues related to such practice. Similar to this, AWON and BEE Group has been implementing an action in three districts of Karnali through financial support of EU. This research is a part of the project to assess the existing context of Chhaupadi and its effects on mobility and leadership status of women. Further it was expected that the findings should be captured as strategies to enhancing leadership of women and finally contribute on eliminating Chhaupadi practice in the project districts. The research focused both quantitative and qualitative approach of data collection from 21 working VDCs of three districts: Julmla, Mugu and Kalikot. The sample for quantitative data were calculated from 1237 women and adolescent girls; and qualitative information were captured through FGD, KII, groups meeting, consultation with district and local committee, and observation of the real context. After the field work, the data were transcribed, tabulated, and analysed based on the theme of research; and the information were categorically analysed with their theme and sub-themes. As findings of research, it was found that the socio-cultural beliefs and values regarding menstruation and Chhaupadi are deeply rooted in the research areas. The female and girls are restricted to enjoy their personal and social life. Similarly, their day to day activities during the menstruation are also affecting by the traditional and social norms. Generally, all these restriction and social boundaries are hampering the mobility of women and girls and negatively contributing on their leadership status. Thematically, the research has explored the following major findings:  Majority of women and adolescent girls (77%) do not enter and stay inside home during their menstruation. The practice of entering inside home while menstruation varies amongst different caste and ethnicities. This rate of such practice is high in Dalits and Chhetri families and low in Janajati, Brahmin and Thakuri families.  98% women and girls do not go to temple or worship ; and 25% of them do not pass nearby of the religious place (such as temple)  There is problem in participating in religious and cultural functions while menstruation. 53% of them do not participate in religious and cultural functions, and those who participate (41.4%) also stay separately  Menstruating women and girls are assigned more outside works. The mean (average) of hour of outside work in normal days is 5.4 hours, but in menstruation period, it is 7.1 hours.  The outside mobility of women and adolescent girls is restricted. During the menstruation period only 34.2 % of women and adolescent girls travel.  There are significant effects of Chhaupadi in leadership development of women. It is found that 30.2% of women/girl who are engaged in local groups/committee do not participate even in group meeting during menstruation period and 62.2 % of women agree that they are not able to participate fully in group's activity due to Chhaupadi practice.  Lacking of gender friendly facilities and unsuitable meeting time in local level institutions are also some hindering factors for ensuring participation of menstruating women in group activities, institutional engagement. Based on the data, information and finding; the research further suggests the following recommendations to build mobility and leadership capacity of women and finally contribute on eliminating the Chhauapdi practice in the research districts as well as in the similar context.  Massive awareness and behaviour change communication at household and community level against the superstition and misunderstanding on Chhaupadi.  Sensitization of local leaders members of local institutions.  Educating and capacity building on women and girls on basic principles of Women Rights and policy provision related to women and girls.  Economic empowerment of women is a means of transformation from deprived condition to quality life.  Recognize and rewards the 'Role model women'  Integrated development approach for empowering women and girls to claim their rights.  Sensitize the new elected local governments on their roles and mandates for rights of women and girls